PENERAPAN METODE DEMONSTRASI TERHADAP HASIL BELAJAR IPS PADA SISWA SEKOLAH DASAR - Sukarlan, Sukarlan; Artini Yasih, Ni Kadek (JEC (Jurnal Edukasi Cendekia), 2019)
The aim of the research is to test a demonstration method that is fun and can be used to study Social Sciences (IPS). This research uses a quantitative approach with a true experimental learning strategy. A total of 34 students were used in this research. The Toro Yamane formula is used in testing tests. Information is collected through multiple choice tests involving an event surrounding the proclamation. The legitimacy and reliability of the research instrument is obtained through a biserial relationship with the quality of the K-R 21 equation, namely the distinguishing power and difficulty index. The post-test result for the test was 74.56, while the control group was 67.65, according to research conducted at SD Negeri 1 Lapero. The test results show a calculated t value of 2.690 > t table and a significant value of 0.011 < 0.05, which means there is a striking difference between the post test results of the experimental group and the control group. Based on the post test differences that emerged, it can be concluded that the demonstration method is more feasible and has a positive impact compared to other learning models implemented in social studies learning for Class V students at SD Negeri 1 Lapero.